Treatment of severe community-acquired pneumonia with oral amoxicillin in under-five children in developing country: a systematic review. - Rashmi Ranjan Das; Rashmi Ranjan Das; Meenu Singh (PLoS ONE)
Objective To assess the evidence regarding efficacy of oral amoxicillin compared to standard treatment for WHO-defined severe community acquired pneumonia in under-five children in developing country. Design Systematic review and meta-analysis of data from published Randomized trials (RCTs). Data sources MEDLINE (1970- July 2012) via PubMed, Cochrane Central Register of Controlled Trials (CENTRAL, The Cochrane Library, Issue 7, July 2012), and EMBASE (1988- June 2012). Methods Eligible trials compared oral amoxicillin administered in ambulatory setting versus standard treatment for WHO-defined severe community acquired pneumonia in children under-five. Primary outcomes were proportion of children developing treatment failure at 48 hr, and day 6. GRADE criteria was used to rate the quality of evidence. Results Out of 281 full text articles assessed for eligibility, 5 trials including 12364 children were included in the meta-analysis. Oral amoxicillin administered either in hospital or community setting is effective in treatment of severe pneumonia and is not inferior to the standard treatment. None of the clinical predictors of treatment failure by 48 hr (very severe disease, fever and lower chest indrawing, and voluntary with-drawl and loss to follow up) was significant between the two groups. The clinical predictors of treatment failure that were significant by day 6 were very severe disease, inability to drink, change of antibiotic, and fever alone. The effect was almost consistent across the studies. Conclusion Though oral amoxicillin is effective in treatment of severe CAP in under-five children in developing country, the evidence generated is of low-quality. More trials with uniform comparators are needed in order to strengthen the evidence.